2012
DOI: 10.17221/73/2011-jfs
|View full text |Cite
|
Sign up to set email alerts
|

Variation of wood density in Turkish hazel (Corylus colurna L.) grown in the Czech Republic

Abstract: ABSTRACT:The aim of this study was to investigate the wood density of Turkish hazel (Corylus colurna L.), an introduced species in the Czech Republic. Sample trees coming from a Czech site were tested for basic wood density and oven-dry density according to Czech National Standards. Four sections were taken from each tree to evaluate the variability of wood density along the stem height and along the stem radius. The mean values for the basic density and the oven-dry density were 544 kg·m -3 and 627 kg·m -3 , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Given that tree species studied were in the same edaphoclimatic conditions, the large differences observed between wood densities of the eighteen tree species could not be directly attributable to environmental conditions, but more to differences between species (Nogueira et al 2007;Gourlet-Fleury et al 2011). These differences could be explained by the intrinsic characteristics of species (Chave et al 2006;Zanne et al 2010;Zeidler, 2012). Guendehou et al (2012) already reported large differences in wood densities in the Lama forest.…”
Section: Basic Wood Densitymentioning
confidence: 97%
“…Given that tree species studied were in the same edaphoclimatic conditions, the large differences observed between wood densities of the eighteen tree species could not be directly attributable to environmental conditions, but more to differences between species (Nogueira et al 2007;Gourlet-Fleury et al 2011). These differences could be explained by the intrinsic characteristics of species (Chave et al 2006;Zanne et al 2010;Zeidler, 2012). Guendehou et al (2012) already reported large differences in wood densities in the Lama forest.…”
Section: Basic Wood Densitymentioning
confidence: 97%
“…Several authors have shown that wood density varies significantly from pith to bark, with a difference that can reach 200 to 300 % in some species (De Castro et al 1993). This is particularly the case for temperate forests (Corylus colurna L. by Zeidler (2012)) and plantations (Eucalyptus grandis × urophylla by Baillères et al (2005)). Radial variation in wood density is associated with competition for light (Wiemann and Williamson 1989).…”
Section: Wood Density Radial Variationmentioning
confidence: 99%
“…Different parts of the plant are valuable source of natural pharmacological compounds (Ceylan et al 2013;Riethmüller et al 2014). Its wood is decorative and has favorable mechanical properties (Korkut et al 2008;Zeidler 2012;2013). In addition, the nuts with high oil content (Erdogan and Aygun 2005) are not only a quality nutrition source for wildlife (Vander Wall 2001) but also used in confectionary industry (Miletić et al 2005).…”
Section: Introductionmentioning
confidence: 99%